2021
DOI: 10.3389/fvets.2021.756764
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Analysis of Outer Membrane Vesicles From a Highly Virulent Strain of Haemophilus parasuis

Abstract: Haemophilus parasuis has emerged as an important bacterial pathogen in pig husbandry, as H. parasuis can coinfect pigs with a variety of pathogenic microorganisms and further cause an aggravation of the disease. It is crucial to investigate its pathogenetic mechanism. Gram-negative bacteria naturally secrete outer membrane vesicles (OMVs), and their potent virulence factors play prominent roles that affect the interaction between bacteria and host. Still, the pathogenesis that is associated with the bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Hfq is an RNA-binding protein that promotes the interaction between sRNAs and their mRNA targets and is vital for the virulence of K. pneumoniae ( 54 ). Furthermore, PGI, manB, and ompA are virulence-associated proteins according to previous literature studies ( 55 ). OMVs also have specific virulence-related activity.…”
Section: Discussionmentioning
confidence: 88%
“…Hfq is an RNA-binding protein that promotes the interaction between sRNAs and their mRNA targets and is vital for the virulence of K. pneumoniae ( 54 ). Furthermore, PGI, manB, and ompA are virulence-associated proteins according to previous literature studies ( 55 ). OMVs also have specific virulence-related activity.…”
Section: Discussionmentioning
confidence: 88%
“…As in the study of [ 6 ], serotype 4 and 13 were found most frequently. Serotype 4 is also the most prevalent serotype in China in pigs suffering from Glässer’s disease [ 31 ], while in nasal swabs of healthy pigs most frequently serotype 7 (20%) and 3 (15%) were detected [ 32 ]. In a recent study concerning the distribution of Gps serotypes in different regions of the world, serotype 5/12 was the most common sort in Canada, China and Vietnam (22–31%) and the second most common sort in Europe (14%) behind serotype 4 (17%) [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In China, P. nicotianae can cause leaf rot disease of Fatsia japonica [6]. In India and Southern Asia, P. nicotianae is one of the main pathogens among Phytophthora spp., and its hosts include, besides citrus and Nicotiana tabacum, Areca catechu, black pepper, Solanum melongena L., Cocos nucifera L., Durio zibethinus L., Psidium guajava L., orchids, Catharanthus roseus, Ananas comosus, Rosa rugosa, Hevea brasiliensis, and fragrant herbs [7]. World agriculture and forestry have undergone major changes as a conjunction of several factors, including globalization and the intensification of international trade, new farming practices, and climate change [8].…”
Section: Introductionmentioning
confidence: 99%